Anxiety Symptoms in Survivors of Critical Illness: A Systematic Review and Meta-Analysis - Nikayin, Sina (Gen Hosp Psychiatry, 2016)
OBJECTIVES: To evaluate the epidemiology of, and post-intensive care unit (ICU) interventions for anxiety symptoms after critical illness METHODS: We searched 5 databases (1970-2015) to identify studies assessing anxiety symptoms in adult ICU survivors. Data from studies using the most common assessment instrument were meta-analyzed. RESULTS: We identified 27 studies (2,880 patients) among 27,334 citations. The Hospital Anxiety and Depression Scale-Anxiety subscale (HADS-A) was the most common instrument (81% of studies). We pooled data at 2-3, 6, and 12-14 month time-points, with anxiety symptom prevalences (HADS-A≥8, 95%CI) of 32%(27-38%), 40%(33-46%), and 34%(25-42%), respectively. In a subset of studies with repeated assessments in the exact same patients, there was no significant change in anxiety score or prevalence over time. Age, gender, severity of illness, diagnosis, and length of stay were not associated with anxiety symptoms. Psychiatric symptoms during admission and memories of in-ICU delusional experiences were potential risk factors. Physical rehabilitation and ICU diaries had potential benefit. CONCLUSIONS: One-third of ICU survivors experience anxiety symptoms that are persistent during their first year of recovery. Psychiatric symptoms during admission and memories of in–ICU delusional experiences were associated with post-ICU anxiety. Physical rehabilitation and ICU diaries merit further investigation as possible interventions.